O currículo e o desenvolvimento de propostas didáticas baseadas na ecologia de saberes: a formação de alunos crítico-reflexivos - Beraldo, Sílvia (2015)
This paper aims at suggesting a new way of organizing a material planning for the English classes for students in the Elementary School, in order to encourage the development of the students critical and reflexive thinking. The theoretical basis for this dissertation is Boaventura de Souza Santos ecology of knowledge theory and Banks multicultural education theory. Both theories principles may help students develop their way of looking at the community where they live in, since these theories are based on the fight against prejudice and alienation. In addition to it, the Socio- Historical-Cultural Activity Theory, as well as the Argumentation theory (LIBERALI, 2013) are the backgrounds of the research and of the analysis here presented. By doing so, this dissertation aims at answering the following questions: (1)How to develop a material planning based on the theory of ecology of knowledge?, and (2) How does the material planning have the potential to develop the multicultural position of the students towards the theme presented during the classes? The data of this research was collected and produced during the classes on prejudice in the fifth grade of the Elementary school in a private school in São Paulo. The Argumentation Theory was applied as a way to analyze the data to find out if there was a change in the development of the critical thinking and position of the students after the material planning was taught. The results of this research show us that we could help develop the students critical thinking. It can be noticed based on the lexical choice the students made and on the use of the scientific knowledge, instead of the ordinary knowledge, to support their opinions about the topic studied: prejudice